2019
DOI: 10.1021/acs.jpcc.8b12567
|View full text |Cite
|
Sign up to set email alerts
|

Tetraphenyethylene-Fused Coumarin Compound Showing Highly Switchable Solid-State Luminescence

Abstract: This paper explores high-contrast mechanoresponsive luminescence (MRL) turn-on materials by combining the features of the coumarin and typical aggregationinduced emission enhancement (AIEE) tetraphenyethylene groups. Therefore, fluorogen C3Ph is obtained by fusing triphenylvinyl and coumarin units, which exhibits typical AIEE characteristics with high solid-state photoluminance (PL) efficiency in the amorphous state. The formation of a unique two-dimensional hydrogen-bonded organic framework (HOF) is responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Compression of the crystal first reduces the intermolecular distances and enhances the intermolecular interactions, which result in the increment of the emission intensities by rigidifying the molecular conformations, and then intermolecular π–π interactions began to form and gradually intensified, which results in the reduction of emission intensity. There are a lot of literature studies investigating the effects of molecular interactions on fluorescence both in ambient pressure and hydrostatic pressure, and the results here are inconsistent with the literature report. ,,, Meanwhile, the calculation also indicates that molecular conformation of PASP becomes more and more twisted in the compression processes as the dihedral angle between the indole and phenol ring became larger gradually, which also contributes to the reducing of the emission. Unfortunately, calculation of PASPTPE using this method failed because of the large number of atoms.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…Compression of the crystal first reduces the intermolecular distances and enhances the intermolecular interactions, which result in the increment of the emission intensities by rigidifying the molecular conformations, and then intermolecular π–π interactions began to form and gradually intensified, which results in the reduction of emission intensity. There are a lot of literature studies investigating the effects of molecular interactions on fluorescence both in ambient pressure and hydrostatic pressure, and the results here are inconsistent with the literature report. ,,, Meanwhile, the calculation also indicates that molecular conformation of PASP becomes more and more twisted in the compression processes as the dihedral angle between the indole and phenol ring became larger gradually, which also contributes to the reducing of the emission. Unfortunately, calculation of PASPTPE using this method failed because of the large number of atoms.…”
Section: Resultscontrasting
confidence: 94%
“…For example, by fusing tetraphenylethene (TPE) with coumarin, Huang and co-workers reported a highly switchable solid-state luminescence "turn-on" type of the mechanofluorochromic material. 26 Very recently, Tang and co-workers not only realized the luminescence turn-on but also observed the molecular motion at room temperature in the solid state by manipulating the reversible formation of π−π interactions through scratching. 27 In these systems, π−π interactions formed first; then, they were destroyed, and the fluorescence was turned "on".…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al synthesized a tetraphenylethylene derivative, 32 (Chart 3), and demonstrated its mechanochromic properties. 116 The crystalline sample of 32 exhibited emission maxima at 545 nm with weak fluorescence. When the crystals of 32 were ground into a powder with the help of quartz glass, it hypsochromically shifted its emission to 529 nm and showed a drastic increase in emission intensity (Fig.…”
Section: Tetraphenylethylene Based Derivativesmentioning
confidence: 98%
“…The aggregation-induced emission (AIE) phenomenon first observed from the aggregation of 1-methyl-1,2,3,4,5-pentaphenylsilole was reported by Tang’s group in 2001 . It plays a critical role in organic light-emitting materials and becomes a hotspot due to its perfect solution to aggregation-caused quenching (ACQ) of chromophoric molecules in the solid state. …”
Section: Introductionmentioning
confidence: 99%